(untitled) (Proceedings of International Conference on Special Education, 2023)
This action research was conducted with the aim of assisting Year Four students in mastering problem-solving skills in the topic of whole numbers and basic operations using the Mathematics Keyword Sheet and CUBES-V strategy. Four students from class 4A of a SJKC (Chinese vernacular school) in Taiping, Perak, were selected as the research subjects based on a diagnostic test. Two participants faced serious difficulties in reading and understanding the questions due to their mother tongue not being Chinese, while the other two participants had a moderate level of understanding but lacked skills in solving mathematical word problems. The research instruments used to collect data for this action research included pre-tests, post-tests, observations, and structured interviews. The quantitative analysis was applied to the data obtained from the pre-test and post-test, while qualitative analysis was used for observations and structured interviews. Two interventions were implemented using the Mathematics Keyword Sheet and CUBES-V strategy. The study findings indicated a significant improvement in the minimum scores of all four students. In terms of attitude, the students transformed from being passive to active, and those who lacked confidence became more assured in answering mathematical word problems. Clearly, the Mathematics Keyword Sheet encompassing three main languages helped the students comprehend the requirements of questions written in Chinese. Additionally, the use of the CUBES-V strategy served as a guideline to assist the students in formulating mathematical sentences from the context of word problems accurately and effortlessly.